Stability Improvement of Humic Acid as Sorbent through Magnetite and Chitin Modification - Bambang Rusdiarso; Rahmat Basuki (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2020)
Stability improvement of humic acid (HA) through modification of HA by chitin (HA-chitin) followed by a coating of HA-chitin on magnetite has been successfully performed. The coated magnetite (magnetite/HA-chitin) was conducted by the co-precipitation method, and the synthesized magnetite/HA-chitin was characterized by FT-IR, XRD, SEM-EDX, and VSM. The successful coated-magnetite by HA-chitin was proved by the appearance of a new band at 1627 cm-1 (FT-IR), the formation of a crystalline phase with characteristic 2θ of magnetite: 30.259° [220]; 35.64° [311]; 42.590° [400]; 57.280° [511]; and 62.896° [440] (XRD), an increasing of carbon content in magnetite/HA-chitin (SEM-EDX), and the ease of magnetite/HA-chitin being attracted to external magnetic fields with magnetic saturation strength 29.3 emu/g (VSM). Stability tests at pH 2.0 - 10.0 prove that magnetite/HA-chitin remains stable as a solid sorbent on average above 80%. Its application to Hg (II) sorption occurred optimum at pH 7.0, where 75.89% Hg (II) is sorbed on 0.1 g of sorbent and agreed well to the pseudo-second-order kinetics model of Ho.